Children’s comprehension of pronouns and definites - Brockmann, Saskia; McConnell, Sara; Hacquard, Valentine; Lidz, Jeffrey (ZAS Papers in Linguistics, 2018)
We present an experiment which tests children’s comprehension of the requirements of use of pronouns and definites. An adult-like use of definites and pronouns imposes different but related requirements. In the case of definites, a unique referent is required in the context, whereas in the case of a pronoun, the referent in the context has to be salient. In this experiment, we use a novel word task to test three-year-olds’ sensitivity to these requirements. Our results show that children are adult-like in their sensitivity to salience in their comprehension of pronouns, compared to definites. However, they failed to show sensitivity to the uniqueness requirement on the use of definites. Keywords: pronouns, definiteness, language acquisition, salience, uniqueness, familiarity.